The functional state of cellular antioxidant defence system of shoots of Arabidopsis thaliana exposed to the chronic ionizing radiation in the Chornobyl exclusion zone - V. S. Morozova; V. A. Kashparov; S. Ye. Levchuk; A. O. Umanska; Ye. V. Bishchuk; L. M. Otreshko (Ядерна фізика та енергетика)
The functional state of the cellular antioxidant defence system of shoots of Arabidopsis thaliana plants that grow in natural conditions in the areas of the Chornobyl Exclusion Zone with the values of the external dose rate of 0.45, 0.61, 1.05, 4.81 and 6.80 μGy/h was evaluated. The decrease of the content of thiobarbituric acid reactive compounds in the shoots of Arabidopsis thaliana was revealed under the external dose rate of 4.81 and 6.80 μGy/h by 38 and 48 %, respectively, compared to this parameter value under the external dose rate of 0.45 μGy/h. In the investigated samples the capacity of guaiacol peroxidase increases, catalase and ascorbate peroxidase decreases significantly with the increase of the external dose rate from 0.45 to 6.80 μGy/h. Probably, revealed changes in the functional state of the cellular antioxidant defence system of the shoots of Arabidopsis thaliana in the conditions of radioactive contamination are adaptive in nature.